3 - An analysis of costs associated with maize storage facilities used by rural smallholder farmers in Uganda - Mautjana, Human; Tibaingana, Anthony; Makombe, Godswill; Kele, Tumo (Africa Development, 2024)
This article assessed the acquisition, maintenance and storage costs associated with different types of storage facilities used by smallholder maize farmers in Uganda, applying cost-based descriptive analysis. These costs influenced the farmers’ decisions about the type of storage facility to use. Poor storage exacerbates losses that result from pests, rats and rot. The findings show that the high costs of acquiring storage and maintenance precluded smallholder maize farmers from accessing good storage. For policy purposes, more investment needs to be directed towards acquiring safe storage to reduce exposure to risk and protect smallholder farmers from food and income insecurity. This article serves to illuminate the storage challenges at the household level to increase food and income security and assuage poverty. The study’s conclusion on the analysis of storage is indicative only. Further research that includes a representative number of storage facilities per storage type needs to be carried out, including a cost-benefit analysis.